Early Activation of Hemostasis during Cardiopulmonary Bypass: Evidence for Thrombin Mediated Hyperfibrinolysis - Teufelsbauer, H; Proidl, Sylvia; Havel, M; Vukovich, Th (Thrombosis and Haemostasis, 1992)
In 14 consecutive patients undergoing cardiopulmonary bypass for coronary bypass surgery the time course of coagulation and fibrinolysis markers were measured, e.g. plasma levels of thrombin-antithrombin III (TAT) complexes, cross-linked fibrin degradation products (X1FDP) and plasmin-α2-antiplasmin complexes (PAP). TAT levels exceeded the 90% baseline percentile already during CPB (after opening of aortic clamp) in 10 patients, whereas PAP and X1FDP exceeded their 90% percentile in only one patient at this time. Concerning fibrinolysis markers PAP and X1FDP the majority of patients showed elevations higher than their 90% baseline percentile only 1 h postoperation. Correlation analysis revealed significant dependencies between TAT levels during and at the end of CPB and PAP levels 1 h postoperation (R = 0.55 and R = 0.56 respectively). Furthermore, 1 h postoperation X1FDP levels were significantly correlated with both TAT and PAP. Peak X1FDP levels at the same time correlated with blood loss via thoracic drains (R = 0.56). Thus, we suggest that hyperfibrinolysis in patients undergoing CPB is at least partly due to hypercoagulation. Clinically, this may implicate that intensified anticoagulation could prevent hyperfibrinolysis and reduce postoperative blood loss.